Populating the Future Families and Reproduction in Speculative Fiction - Farstad, Britt (Kriterium, 2023)
Speculative fiction opens doors for imagining beyond what is possible, conventional or acceptable. Speculative fiction has an acute ear for the social, the scientific and for political developments and change, all of which are prominent topics. Reproduction and parenthood are pertinent social questions that are constantly renegotiated in various arenas. By investigating representations of family-making and reproduction in speculative fiction, the research presented in Populating the Future: Families and Reproduction in Speculative Fiction not only adds to the field of speculative fiction scholarship, but also contributes to the more general discussion about reproduction and parenting. Speculative fiction operates as thought laboratories that make connections between discourses visible. It highlights power structures that can be difficult to detach and represents difficult and abstract issues more concretely. As such, speculative fiction demonstrates the complex entanglement of reproduction with issues of gender, power and agency. By facilitating thought experiments and illustrating alternatives, speculative fiction also enables the representation of new family structures and reproductive technologies, thus paving the way for discussions about various practices and their possible consequences. Due to its multidisciplinary approach, this book will be of value to scholars and students of various disciplines, such as literature studies, philosophy, ethics, political science, the social sciences and gender studies. It will also be a useful resource in teacher training programmes, as well as to a more general audience interested in speculative literature, politics, society, gender and ethics.